2009
DOI: 10.1007/s12043-009-0126-4
|View full text |Cite
|
Sign up to set email alerts
|

Isospectrality of conventional and new extended potentials, second-order supersymmetry and role of % MathType!MTEF!2!1!+- % feaagaart1ev2aaatCvAUfeBSjuyZL2yd9gzLbvyNv2CaerbuLwBLn % hiov2DGi1BTfMBaeXatLxBI9gBqj3BWbIqubWexLMBb50ujbqegm0B % 1jxALjharqqtubsr4rNCHbGeaGqiVu0Je9sqqrpepC0xbbL8F4rqqr % Ffpeea0xe9Lq-Jc9vqaqpepm0xbba9pwe9Q8fs0-yqaqpepae9pg0F % irpepeKkFr0xfr-xfr-xb9adbaqaaeGaciGaaiaabeqaamaabaabaa % GcbaWefv3ySLgznfgDOfdarCqr1ngBPrginfgDObYtUvgaiuaacqWF % pepucqWFtepvaaa!46A4! $$ \mathcal{P}\mathcal{

Abstract: We develop a systematic approach to construct novel completely solvable rational potentials. Second-order supersymmetric quantum mechanics dictates the latter to be isospectral to some well-studied quantum systems. PT symmetry may facilitate reconciling our approach to the requirement that the rationally-extended potentials be singularity free. Some examples are shown.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
79
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 98 publications
(84 citation statements)
references
References 31 publications
5
79
0
Order By: Relevance
“…After noting [3] that the first extended potentials enlarged the class of known translationally shape invariant potentials in supersymmetric quantum mechanics (SUSYQM) [4,5,6], it appeared convenient to use a SUSYQM technique to construct some additional examples of EOP and potentials [7,8], in agreement with previous works on algebraic deformations of shape invariant potentials [9,10].…”
supporting
confidence: 63%
“…After noting [3] that the first extended potentials enlarged the class of known translationally shape invariant potentials in supersymmetric quantum mechanics (SUSYQM) [4,5,6], it appeared convenient to use a SUSYQM technique to construct some additional examples of EOP and potentials [7,8], in agreement with previous works on algebraic deformations of shape invariant potentials [9,10].…”
supporting
confidence: 63%
“…After the introduction of the first families of exceptional orthogonal polynomials (EOP) in the context of Sturm-Liouville theory [11,12], the realization of their usefulness in constructing new SI extensions of ES potentials in quantum mechanics [13,14,15], and the rapid developments that followed in this area [16,17,18,19,20,21,22,23,24,25,26,27,28,29,30], it soon appeared that only some of the well-known SI potentials led to rational extensions connected with EOP. In this category, one finds the radial oscillator [13,15,16,17,18,22,23,24], the Scarf I (also called trigonometric Pöschl-Teller or Pöschl-Teller I) [13,15,16,17,22,24], and the generalized Pöschl-Teller (also termed hyperbolic Pöschl-Teller or Pöschl-Teller II) [14,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…In this category, one finds the radial oscillator [13,15,16,17,18,22,23,24], the Scarf I (also called trigonometric Pöschl-Teller or Pöschl-Teller I) [13,15,16,17,22,24], and the generalized Pöschl-Teller (also termed hyperbolic Pöschl-Teller or Pöschl-Teller II) [14,16,17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The investigations were extended to some Natanzon-class potentials too [27][28][29] and even to potentials solved in terms of exceptional orthogonal polynomials [30]. It was found that some potentials have strictly real energy spectrum, while others support complex conjugate energy eigenvalues too.…”
Section: Introductionmentioning
confidence: 99%